Collection and transportation of oil palm FFB during harvesting - Bardaie, Mohd Zohadie; Wan Ismail, Wan Ishak (Incorporated Society of Planters, 1982)

(untitled)
Malaysia is the principal world producer of palm oil. In 1981, it produces 2.7 million tonnes of palm oil, and it is estimated that the production in 1982 will increase to 2.9 million tonnes. The total area planted with oil palm throughout the country in 1981 is about 992000 hectares. One major problem currently faced by the palm oil industry is the unavailability of adequate labour supply for the handling of heavy and strenuous tasks such as the harvesting offresh fruit bunches (ffb) on oil palm plantations. This problem is caused mainly by the migration of labour to urban areas. This labour shortage has caused the plantation sector to lose a substantial amount of income. According to a survey conducted by the united planting association of malaysia (upam) in 1980, the crop losses were 170 000 tonnes. The report was based on the december 1980 prices, in that the losses suffered by the plantations came to $54 million (anon, 1981).